Homeland, emotions, and identity: Constructing the place attachment of young overseas Chinese relatives in the returned Vietnam-Chinese community - Shu, Zhangwen; Du, Yuan; Li, Xuzhou (Frontiers in Psychology, 2023)
Little attention has been paid to the place attachment and homeland construction for refugees and their descendants in China. This study investigates the process by which the place attachment of Young Overseas Chinese Relatives is shaped in the context of resettlement sites. This qualitative research employed ethnographic fieldwork, and the author collected local literature and materials from February to December 2019 through participatory observation, in-depth interviews, and questionnaires. It is believed that the construction of a new homeland in the community, the emotional experience of the Young in childhood, and the cultural logic of place attachment shape place attachment. The process by which place attachment is shaped is interwoven with homeland construction, which indicates that the living state and mentality of the Young are becoming increasingly stable. The Young developed different mentalities on the basis of traditional Confucian culture in responding to the socio-cultural environments. The resettlement site has become a homeland to which young persons are solidly attached, people give this site meanings and experience certain emotions regarding it, which generates place identity and begins the process of homeland construction.